Saintek : Analisis Tren dan Kebutuhan Industri Masa Depan: Penelitian - Andini Putri, Dwi; Azzahra, Dalfa; Isnaeni, Halimah; Patoni (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to explore science and technology programs that are less popular, despite offering promising career opportunities, referring to SNPMB 2024 data. Using a descriptive-quantitative approach conducted through Google Colab, the collected data was processed and visualized in the form of pie charts, bar charts, scatter plots, histograms, heatmaps, and word clouds. The findings show that programs such as Geophysics, Physics, and Biology, as well as several engineering majors, have a low number of applicants, while the demand for workers in these fields is actually increasing in line with the development of digitalization and Industry 4.0. The results of this study highlight that the low level of interest is not in line with the existing career opportunities, so it is very important to improve career literacy among prospective students.